Grammar errors in the writing of Iraqi English language learners - Al-Shujairi, Yasir Bdaiwi Jasim; Tan, Helen (Australian International Academic Centre, 2017)
Several studies have been conducted to investigate the grammatical errors of Iraqi postgraduates and undergraduates in their academic writing. However, few studies have focused on the writing challenges that Iraqi pre-university students face. This research aims at examining the written discourse of Iraqi high school students and the common grammatical errors they make in their writing. The study had a mixed methods design. Through convenience sampling method, 112 compositions were collected from Iraqi pre-university students. For purpose of triangulation, an interview was conducted. The data was analyzed using Corder’s (1967) error analysis model and James’ (1998) framework of grammatical errors. Furthermore, Brown’s (2000) taxonomy was adopted to classify the types of errors. The result showed that Iraqi high school students have serious problems with the usage of verb tenses, articles, and prepositions. Moreover, the most frequent types of errors were Omission and Addition. Furthermore, it was found that intralanguage was the dominant source of errors. These findings may enlighten Iraqi students on the importance of correct grammar use for writing efficacy.